Synthesis and antimicrobial activity of novel 5-aminoimidazole-4-carboxamidrazones - Ribeiro, Ana Isabel F. (2014)
A mild and simple method was developed to prepare a series of fifteen 5-aminoimidazole 4-carboxamidrazones, starting from the easily accessible 5-amino-4-cyanoformimidoyl imidazoles. The antimicrobial activity of these novel amidrazones was screened against Gram positive (S. aureus) and Gram negative (E. coli, P. aeruginosa) bacteria and Candida sp. (C. albicans, C. krusei, C. parapsilosis). Only a subset of compounds displayed fair-moderate activity against S. aureus and E. coli but all exhibited activity against Candida sp. The three most potent antifungal compounds were further tested against C. neoformans, A. fumigatus and three dermatophytes (T. rubrum, T. mentagrophytes, M. gypseum). These three hit compounds strongly inhibited C. krusei and C. neoformans growth, although their activity on filamentous fungi was very weak when compared to the activity on yeasts.